Effectiveness of strontium/silver-based titanium surface coatings in improving antibacterial and osteogenic implant characteristics: a systematic review of in-vitro studies - Kheirmand-Parizi, Marjan; Doll-Nikutta, Katharina; Gaikwad, Amit; Denis, Hannah; Stiesch, Meike (Frontiers in Bioengineering and Biotechnology, 2024)
Due to the high incidence of implant failures, dual functionalization of titanium surfaces with antibacterial and osteogenic agents, like silver (Ag) and strontium (Sr), has gained significant attention in recent years. However, so far, the combined antibacterial and osteoinductive effectiveness of Ag/Srbased titanium surface coatings has only been analyzed in individual studies. Therefore, this systematic review aims to evaluate the existing scientific literature regarding the PICOS question "Does dual incorporation of strontium/silver enhances the osteogenic and anti-bacterial characteristics of Ti surfaces in vitro?". As a result of a web-based search adhering to the PRISMA Guidelines using three electronic databases (PubMed, Scopus, and Web of Science) until March 31, 2023, a total of 69 publications were identified as potentially relevant and 17 of which were considered appropriate for inclusion into this review. In all included publications, the use of Sr/Ag combination showed enhanced osteogenic and antibacterial effects, either alone or in combination with other agents. Moreover, the combination of Sr and Ag shows potential to synergistically enhance these effects. Nevertheless, further studies need to validate these findings under clinically more relevant conditions and evaluate the mechanism of antimicrobial and osteogenic activity of Sr/Ag combination.